ER predicts poor prognosis in male lung squamous cell cancer of stage IIIA-N2 disease after sequential adjuvant chemoradiotherapy - Yang, Xue; Wang, Lili; Jin, Xiangfeng; Xu, Rongjian; Yu, Zhuang; Li, Hongmei; Lu, Haijun; An, Ning (Frontiers in Oncology, 2023)
The efficacy of postoperative radiotherapy (PORT) is still unclear in non-small cell lung cancer (NSCLC) patients with pIIIA-N2 disease. Estrogen receptor (ER) was proven significantly associated with poor clinical outcome of male lung squamous cell cancer (LUSC) after R0 resection in our previous study. A total of 124 male pIIIA-N2 LUSC patients who completed four cycles of adjuvant chemotherapy and PORT after complete resection were eligible for enrollment in this study from October 2016 to December 2021. ER expression was evaluated using immunohistochemistry assay. The median follow-up was 29.7 months. Among 124 patients, 46 (37.1%) were ER positive (stained tumor cells≥1%), and the rest 78 (62.9%) were ER negative. Eleven clinical factors considered in this study were well balanced between ER+ and ER- groups. ER expression significantly predicted a poor prognosis in disease-free survival (DFS, HR=2.507; 95% CI: 1.629-3.857; log-rank p=1.60×10-5). The 3-year DFS rates were 37.8% with ER- vs. 5.7% with ER+, with median DFS 25.9 vs. 12.6 months, respectively. The significant prognostic advantage in ER- patients was also observed in overall survival (OS), local recurrence free survival (LRFS), and distant metastasis free survival (DMFS). The 3-year OS rates were 59.7% with ER- vs. 48.2% with ER+ (HR, 1.859; 95% CI: 1.132-3.053; log-rank p=0.013), the 3-year LRFS rates were 44.1% vs. 15.3% (HR=2.616; 95% CI: 1.685-4.061; log-rank p=8.80×10-6), and the 3-year DMFS rates were 45.3% vs. 31.8% (HR=1.628; 95% CI: 1.019-2.601; log-rank p=0.039). Cox regression analyses indicated that ER status was the only significant factor for DFS (p=2.940×10-5), OS (p=0.014), LRFS (p=1.825×10-5) and DMFS (p=0.041) among other 11 clinical factors. PORT might be more beneficial for ER negative LUSCs in male, and the examination of ER status might be helpful in identifying patients suitable for PORT.